Interaction of a dengue virus NS1-derived peptide with the inhibitory receptor KIR3DL1 on natural killer cells. (24th November 2015) - Townsley, E; O'Connor, G; Cosgrove, C; Woda, M; Co, M; Thomas, S J; Kalayanarooj, S; Yoon, I-K; Nisalak, A; Srikiatkhachorn, A; Green, S; Stephens, H A F; et al.
Summary: Killer immunoglobulin-like receptors (KIRs) interact with human leucocyte antigen (HLA) class I ligands and play a key role in the regulation and activation of NK cells. The functional importance of KIR–HLA interactions has been demonstrated for a number of chronic viral infections, but to date only a few studies have been performed in the context of acute self-limited viral infections. During our investigation of CD8 + T cell responses to a conserved HLA-B57-restricted epitope derived from dengue virus (DENV) non-structural protein-1 (NS1), we observed substantial binding of the tetrameric complex to non-T/non-B lymphocytes in peripheral blood mononuclear cells (PBMC) from a long-standing clinical cohort in Thailand. We confirmed binding of the NS1 tetramer to CD56 dim NK cells, which are known to express KIRs. Using depletion studies and KIR-transfected cell lines, we demonstrated further that the NS1 tetramer bound the inhibitory receptor KIR3DL1. Phenotypical analysis of PBMC from HLA-B57 + subjects with acute DENV infection revealed marked activation of NS1 tetramer-binding natural killer (NK) cells around the time of defervescence in subjects with severe dengue disease. Collectively, our findings indicate that subsets of NK cells are activated relatively late in the course of acute DENV illness and reveal a possible role for specific KIR–HLA interactions in the modulation of disease outcomes.